2009
DOI: 10.1590/s0036-36342009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Factores relacionados con el descontrol de la presión arterial

Abstract: Hypertension is well-controlled in the majority of patients. Patient-related factors are important in uncontrolled hypertension; however, health care system characteristics also play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
2
5
1
7
Order By: Relevance
“…A systematic review has shown that individuals performing regular physical activities tend to gain less weight and to be less overweight and obese (28) . This may explain the high prevalence of inadequate control of BP among individuals who had increased BMI, before and after adjustment, similar to that reported by Mejía-Rodríguez et al (22) . It is known that reducing weight contributes to BP control and allows for reducing the dosage of antihypertensive drugs in hypertensive patients (29) .…”
Section: Discussionsupporting
confidence: 85%
“…A systematic review has shown that individuals performing regular physical activities tend to gain less weight and to be less overweight and obese (28) . This may explain the high prevalence of inadequate control of BP among individuals who had increased BMI, before and after adjustment, similar to that reported by Mejía-Rodríguez et al (22) . It is known that reducing weight contributes to BP control and allows for reducing the dosage of antihypertensive drugs in hypertensive patients (29) .…”
Section: Discussionsupporting
confidence: 85%
“…One Mexican cross-sectional study evaluated the impact of being treated by a specialist on HT control [43]. This study found a moderately increased risk of uncontrolled HT in hypertensive individuals treated by non-specialist physicians (general practitioners) compared to those treated by specialists (adjusted OR 1.43, 95% CI 1.20–1.71).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 33 studies that provided contextual information, this varied from single phrases or sentences to more detailed contextual information (Box 2). 28 of 53 included studies gave no description of the national or regional health system where the study was conducted [22],[26],[31]–[34],[37][39],[43],[46],[53][56],[58][62],[66]–[68],[72],[74][76]. Where a description of the health system was given it was in most cases limited to a brief sentence on insurance coverage or financing arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…Nuestros resultados apoyan a aquellos de un estudio previo en derechohabientes del IMSS con HAS, donde fue documentado un incremento promedio estadísticamente significativo de 3% en el descontrol de presión arterial por el aumento de cada unidad de IMC. 30 Lamentablemente, la naturaleza transversal de nuestro trabajo no permite saber si la elevada prevalencia de sobrepeso refleja fallas en los procesos de control del paciente o si son producto de las altas prevalencias de este fenómeno en la población al momento del diagnóstico. Los resultados presentados aquí deben interpretarse a la luz de algunas limitaciones.…”
Section: Discussionunclassified
“…Por un lado, nuestros análisis no consideran el número ni el tipo de medicamentos prescritos para cada paciente. Se sabe que en el caso de HAS el control metabólico mejora 48% cuando se consumen dos o más fármacos, 30 no obstante, de acuerdo con el análisis presentado en un trabajo previo, 29 prácticamente todos los pacientes de la presente muestra tenían registro de prescripción de medicamento (96% de pacientes diabéticos y 98 de hipertensos) pero dada la naturaleza del estudio no fue posible verificar si los pacientes efectivamente los consumían. Por otro lado, si bien hay factores relacionados con los médicos que también se han asociado con un…”
Section: Discussionunclassified